Inhibition of Burkholderia cenocepacia H111 quorum sensing system by environmental bacterial isolates - Wahjudi, Mariana; Kurniawan, W D; Gultom, M T; Artadana, Ida Bagus Made; Mohamad Puad, Noor Illi (IOP Publishing, 2019)
Burkholderia cenocepacia H111 is an opportunistic pathogen which is difficult to eradicate due to its virulence factors, specifically biofilm. The ability of B. cenocepacia to form biofilm is regulated by quorum sensing (QS) system using a signal molecule. Environtmental bacteria often showed the ability to inhibit the QS of other species because they have special and unique metabolites or enzymes. In previous research several environtmental bacteria was isolated from few places in Java Island. However, until now the potential of these bacteria have not been investigated yet. This study was conducted with the aim to investigate the effect of these environmental bacterial isolates, i.e. Bacillus sp., Stenotrophomonas maltophilia, Enterobacter ludwigii and Kosakonia radicincitans on quorum sensing system of B. cenocepacia H111, particularly on quantities of acyl homoserine lactones (AHLs) and biofilm that were produced. The quantity of AHL molecule is measured by biosensor assay using Escherichia coli JM109 pSB401 while the quantity of biofilm formation was quantified by crystal violet method. The result showed that supernatants of all these environtmental bacteria have no impact in decreasing of AHL nor biofilm. On the other hands, all the crude extracts showed a reduction either to AHL molecule and biofilm formation. The Bacillus sp. crude extract revealed the most reducing effect, with 84 % for AHL molecule and 71 % for biofilm. It can be concluded that crude extracts of all environmental bacteria have quorum quenching activity to B. cenocepacia H111 cells, specifically in reducing AHL levels and biofilm quantity. Crude extract from Bacillus sp. gave the highest inhibitory effect.